Tunable mode-locked soliton fibre laser based on single-walled carbon nanotubes - Ahmad, Harith; Reduan, Siti Aisyah; Ismail, Mohammad Faizal; Thambiratnam, Kavintheran (Kvantovaya Elektronika and Turpion Ltd, 2018)
A soliton fibre laser with a tunable mode-locked output is proposed and demonstrated. The laser is based on a conventional erbium-doped fibre and uses single-walled carbon nanotubes (SWCNTs) as a saturable absorber (SA). Tuning is performed using a tunable Mach – Zehnder filter (TMZF). The SWCNT-based SA has a modulation depth of ~19.0 % and saturation intensity of 45.3 MW cm –2 . Mode-locking begins at a pump power of 6.0 mW and allows pulsed outputs to be generated from 1550 nm to 1566 nm. The 3 dB bandwidth and pulse duration of the output pulse vary slightly from 6.34 nm to 6.90 nm and from 0.51 ps to 0.56 ps, respectively, which results in the corresponding time-bandwidth product varying from 0.40 to 0.46. The results suggest that the proposed laser would have significance advantages in many applications, particularly spectroscopy and telecommunications.